The Bowel CLEANsing National Initiative: A Low-Volume Same-Day Polyethylene Glycol (PEG) Preparation vs Low-Volume Split-Dose PEG With Bisacodyl or High-Volume Split-Dose PEG Preparations—A Randomized Controlled Trial. (29th December 2020) - Barkun, Alan N.; Martel, Myriam; Epstein, Ian L.; Hallé, Pierre; Hilsden, Robert J.; James, Paul D.; Rostom, Alaa; Sey, Michael; Singh, Harminder; Sultanian, Richard; Telford, Jennifer J.; von Renteln, Daniel
Abstract : INTRODUCTION: Bowel cleanliness has been shown to be superior with split-dose vs nonsplit preparations; we aimed to directly assess the poorly characterized comparative efficacies of split-dose vs same-day polyethylene glycol (PEG) regimens. METHODS: In this study, one of a series of randomized trials performed across 10 Canadian endoscopy units, patients undergoing colonoscopies between 10:30 and 16:30 were allocated to PEG low-volume same-day (15 mg bisacodyl the day before, 2 L the morning of the procedure), low-volume split-dose (15 mg bisacodyl the day before, 1 L + 1 L), or high-volume split-dose (2 L + 2 L). Coprimary endpoints were adequate bowel cleansing based on the Boston Bowel Preparation Scale using in turn different threshold cutoffs. RESULTS: Overall, 1, 750 subjects were randomized equally across the 3 groups, with no differences in adequate bowel cleanliness rates (low-volume same-day, 90.5%; high-volume split-dose, 92.2%; P = 0.34; and low-volume split-dose, 87.9%; P = 0.17) for the Boston Bowel Preparation Scale ≥6 and 2 for each segment. Willingness to repeat the preparation was not significantly different between low-volume same-day (91.0%) and low-volume split-dose (92.5%; P = 0.40) but was greater than the high-volume split-dose (68.9%; P < 0.01). No significant differences were noted for withdrawal time, cecal intubation, or polyp detection rates. DISCUSSION: In this large randomized trial of PEG regimens, low-volume same-day resulted in similar bowel cleanliness compared with high-volume or low-volume split-dosing. Willingness to repeat and tolerability were superior with low-volume same-day compared with high-volume split-dose and similar to low-volume split-dose.